Legal Conscience and the Pressure of the Formal Law System - Budiono, Arief; Prasetyo, Yogi; Wardiono, Kelik; Yuspin, Wardah; Dimyati, Khudzaifah; Iriani, Dewi (Տիգրան Մեծ)
Society has concerns when there are actions that are not according to the law. Law enforcers must develop legal mindsets to fill the legal void in society by providing legal practice or legal rationing through legal interpretation. This paper aims to analyze: (1) What is the role of logic and legal rationing in achieving justice? (2) Describe the legal condition and the image of the pressure of formal law in society! And (3) What roles do judges have in justly enforcing the law? The results of the study found that (1) A just decision with a conscience will result in quality decisions. They are progressive as opposed to blindly following formality, (2) In reality, the law no longer represents high virtues, but rather, it represents political interests to sustain some people‟s domination. The positivist legal system should develop a new alternative structure that is less rigid, (3) Judges have the freedom to choose the best and most accurate alternative in reaching a just decision. In conclusion, judges must be able to make decisions based on conscience without ignoring the formal law to fulfil society‟s need for justice.
Keywords: Philosophy of law